A Flexible Carbon Nanotube Sen‐Memory Device. Issue 9 (24th January 2020) - Qu, Ting‐Yu; Sun, Yun; Chen, Mao‐Lin; Liu, Zhi‐Bo; Zhu, Qian‐Bing; Wang, Bing‐Wei; Zhao, Tian‐Yang; Liu, Chi; Tan, Jun; Qiu, Song; Li, Qing‐Wen; Han, Zheng; et al.
Abstract: In a modern electronics system, charge‐coupled devices and data storage devices are the two most indispensable components. Although there has been rapid and independent progress in their development during the last three decades, a cofunctionality of both sensing and memory at single‐unit level is yet premature for flexible electronics. For wearable electronics that work in ultralow power conditions and involve strains, conventional sensing‐and‐memory systems suffer from low sensitivity and are not able to directly transform sensed information into sufficient memory. Here, a new transformative device is demonstrated, which is called "sen‐memory", that exhibits the dual functionality of sensing and memory in a monolithic integrated circuit. The active channel of the device is formed by a carbon nanotube thin film and the floating gate is formed by a controllably oxidized aluminum nanoparticle array for electrical‐ and optical‐programming. The device exhibits a high on–off current ratio of ≈10 6, a long‐term retention of ≈10 8 s, and durable flexibility at a bending strain of 0.4%. It is shown that the device senses a photogenerated pattern in seconds at zero bias and memorizes an image for a couple of years. Abstract : Transformative nanodevices incorporate emerging nanotechnologies to meet future data‐intensive applications. A new flexible carbon nanotube transformative device named "sen‐memory" is developed, showing fused sensing‐and‐memory functionality and large scalability. The sen‐memory matrix realizes an in situ writing of optical data into nonvolatile memory without an auxiliary gate bias and the photogenerated pattern can be stored for a couple of years.